2004
DOI: 10.1097/01.shk.0000135255.59817.8c
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Resuscitation of Multiple Hemorrhages Using Crystalloid and Colloids

Abstract: Hypotensive resuscitation has been advocated as a better means to perform field resuscitation of penetrating trauma. Our hypothesis is that hypotensive resuscitation using either crystalloid or colloid provides equivalent or improved metabolic function while reducing the overall fluid requirement for resuscitation of hemorrhage. We compared hypotensive and normotensive resuscitation of hemorrhage using lactated Ringer's (LR) with hypotensive resuscitation using Hextend (Hex), 6% hetastarch in isotonic buffered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 21 publications
1
57
0
1
Order By: Relevance
“…The mortality rate (7.3%) was the same for both groups of patients. However, comparison of Injury Severity Scores 26 indicated that patients in the low group (scores, [16][17][18][19][20][21][22][23][24] were more severely injured (P = .02) than were patients in the conventional group (scores, 9-15). Thus, permissive hypotensive resuscitation may benefit restoration of blood circulation and cause a modest increase in blood pressure (reducing the risk of additional blood loss due to continued bleeding or rebleeding) with minimal fluid requirements.…”
Section: Studies Of Permissive Hypotension In Humansmentioning
confidence: 94%
See 1 more Smart Citation
“…The mortality rate (7.3%) was the same for both groups of patients. However, comparison of Injury Severity Scores 26 indicated that patients in the low group (scores, [16][17][18][19][20][21][22][23][24] were more severely injured (P = .02) than were patients in the conventional group (scores, 9-15). Thus, permissive hypotensive resuscitation may benefit restoration of blood circulation and cause a modest increase in blood pressure (reducing the risk of additional blood loss due to continued bleeding or rebleeding) with minimal fluid requirements.…”
Section: Studies Of Permissive Hypotension In Humansmentioning
confidence: 94%
“…20 A systematic meta-analysis of preclinical data (52 animal trials) 21 indicated an increased adjusted relative risk of death, from 0.69 to 1.80, when aggressive resuscitation was used in animals with less severe hemorrhage (ie, tail resection). In other trials, 16,17 attempts to increase MAP to 80 mm Hg with fluid resuscitation in animals with established hypovolemic shock were associated with decreased oxygen supply to the tissues, metabolic acidosis, and a poor outcome.…”
Section: Experimental Assessment Of Permissive Hypotension In Animalsmentioning
confidence: 99%
“…Consequently, the models used, while providing valuable information for a debate regarding civilian resuscitation, were less relevant to a potential military situation since the injury models are considered unsurvivable in a battlefield setting and military evacuation timelines can be considerably longer. With longer resuscitation timelines, tissue hypoperfusion, a serious limitation of the hypotensive strategy, assumes greater clinical significance ultimately leading to ischaemic damage [30,31]. The clinical evidence supporting hypotensive resuscitation is limited to short evacuation times to surgical care, e.g.…”
Section: Forward (Pre-hospital) Resuscitationmentioning
confidence: 99%
“…For the past 4 decades, the standard approach to the hypotensive trauma victims suffering from hemorrhagic shock to maintain adequate tissue perfusion and oxygenation is massive infusion of crystalloid solutions such as Ringer's lactate because blood products are not readily available in the pre-hospital settings (Stadlbauer et al, 2003, Stern 2001 Animal studies have shown that try to enhance normal blood pressure by early aggressive fluid resuscitation during uncontrolled hemorrhage of liver or spleen causes increased mortality (Rafie et al, 2004;Solomonov et al, 2000). Suggested mechanisms for increased mortality include diluted coagulating factors, increased blood pressure and disruption of an effective clot followed by secondary hemorrhage (Kowalenko et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Lee et al (2007) demonstrated that delayed resuscitation also may be detrimental in terms of cytokine production profile and histopathological changes. Hence, some authors suggest that "limited" or "hypotensive" resuscitation may be preferable in the trauma patients to avoid detrimental effects of early aggressive or delayed fluid infusion (Kowalenko et al, 1992;Lee et al, 2007;Rafie et al, 2004;Stern, 2001).…”
Section: Discussionmentioning
confidence: 99%